2015
DOI: 10.1136/bmjopen-2015-009116
|View full text |Cite
|
Sign up to set email alerts
|

Informed shared decision-making programme on the prevention of myocardial infarction in type 2 diabetes: a randomised controlled trial

Abstract: ObjectiveTo evaluate an informed shared decision-making programme (ISDM-P) for people with type 2 diabetes under high fidelity conditions.DesignRandomised, single-blinded trial with sham control intervention and follow-up of 6 months.SettingSingle-centre diabetes clinic providing care according to the national disease management programme in Germany.Participants154 people with type 2 diabetes without diagnosis of ischaemic heart disease or stroke.InterventionsThe ISDM-P is executed by diabetes educators. Core … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 49 publications
2
65
0
1
Order By: Relevance
“…Three of the PtDAs [31,39,41] were evaluated in multiple studies. One PtDA [41] was used in two RCTs [23,34] as part of a more complex informed shared decision-making intervention, whereas the remaining nine were stand-alone PtDAs. Four PtDAs focused on involving people with Type 2 diabetes in decisions about medication, four focused on prioritizing and setting treatment goals (such as glucose or BP control) or lifestyle goals (such as smoking cessation, healthy eating or physical activity), whereas two PtDAs focused on both.…”
Section: Decision Aidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Three of the PtDAs [31,39,41] were evaluated in multiple studies. One PtDA [41] was used in two RCTs [23,34] as part of a more complex informed shared decision-making intervention, whereas the remaining nine were stand-alone PtDAs. Four PtDAs focused on involving people with Type 2 diabetes in decisions about medication, four focused on prioritizing and setting treatment goals (such as glucose or BP control) or lifestyle goals (such as smoking cessation, healthy eating or physical activity), whereas two PtDAs focused on both.…”
Section: Decision Aidsmentioning
confidence: 99%
“…In one study, risk of bias assessment was based only on data presented in a conference abstract without contacting the corresponding authors [23]. Overall, eight studies were considered low risk [22,24,28,29,31,[34][35][36], four raised some concerns [23,30,33,37] and three studies were deemed at high risk of bias [25,27,38] due to concerns about the randomization process [25], high attrition rate [38] and inclusion of a participating practice after randomization [27].…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, a recent randomised controlled trial on patients with T2DM has demonstrated promising results of an informed shared decision-making programme, including a decision aid, with regard to patients' risk comprehension for myocardial infarction. 38 …”
Section: Implications For Practice and Researchmentioning
confidence: 99%
“…Broadly defined, SDM approaches have been applied in a wide variety of chronic diseases including diabetes, [5][6][7] hypertension, [8,9] cardiovascular disease, [10][11][12] osteoarthritis, [13] asthma, [14] fibromyalgia, [15] and depression. [16,17] A diagnosis of cancer, however, challenges patients with an array of treatment options often far more complex than other chronic diseases.…”
Section: Introductionmentioning
confidence: 99%